Communicating User Experience: Applying Local Strategies Research to Digital Media Design - Milburn, Trudy (2015)
Communicating User Experience illustrates how the use of Local Strategies Research (LSR) methodologies enables designers to understand the cultural implications for user actions and practices in a...
Keywords: dept.aa

Going global: the introduction of the Asian isopod Ianiropsis serricaudis Gurjanova (Crustacea: Peracarida) to North America and Europe - Hobbs, Niels-Viggo; Lazo-Wasem, Eric; Faasse, Marco; Cordell, Jeffery R.; Chapman, John W.; Smith, Carter S.; Prezant, Robert; Shell, Rebecca; Carlton, James T. (Aquatic Invasions, 2015)
The Asian isopod Ianiropsis serricaudis is now well established in fouling communities, often associated with introduced ascidians, throughout the Northern Hemisphere but has gone largely unnoticed because of its diminutive size (typically less than 3 mm in length) and the difficulties of identifying small peracarid crustaceans. Known locations include the northeastern Pacific (Puget Sound, San Francisco Bay, and Monterey Bay), the northwestern Atlantic (from the Gulf of Maine to Barnegat Bay, NJ), and the northeastern Atlantic (England and the Netherlands). We predict that this species is widespread along North America and European coasts, and may already be introduced to cold temperate waters of the Southern Hemisphere as well.
11 citations (Crossref) [2023-10-31]
Keywords: Arthropoda; Carcinogenicity; Carcinology; Europe; Ianiropsis serricaudis; Isopoda; Shellfish; ballast water; dept.aa; fouling; introduced species; marine; shipping

Comparative Shell Microstructure of Two Species of Tropical Laternulid Bivalves from Kungkrabaen Bay, Thailand with After-Thoughts on Laternulid Taxonomy - Prezant, Robert S.; Shell, Rebecca M.; Wu, Laying (American Malacological Bulletin, 2015)
The anomalodesmatan family Laternulidae represents a group of bivalves with a very few well-known taxa and many more poorly known taxa. Laternula rostrata (G. B. Sowerby, 1839) and L. anatina (Linnaeus, 1758) occur in close proximity to each other in and along the margins of mangroves of Kungkrabaen Bay, Thailand. Laternula rostrata resides in soft to sandy sediments often within the interstices of mangrove roots located in more open portions of the mangrove mud flat. Laternula anatina lives deeper in the mangrove in more protected environs. Laternula anatina is a smaller bivalve that has a variable shell outline, sometimes a wrinkled shell appearance, thicker periostracum, and frequently extensive umbonal erosion. Both species have high concentrations of external shell spinules anteriorly and closer to the umbos (i.e., in juvenile shell) reflecting functionality in retaining an infaunal position. The larger L. rostrata is thinner shelled and more fragile; has more distinct and longer shell spinules composed of flattened lathes; a glossy external appearance; a longer umbonal slit; and a deeper pallial sinus. Additionally, L. rostrata has a saddle-shaped lithodesma; a lithodesma is absent in L. anatina as is typical of most laternulids. Shell microstructure of both is prismatonacreous, typical of the group, but the prismatic layer is thin and appears truncated into small blocky and/or granular columns in transitional zones. The bulk of the shell is tightly packed sheet nacre. The growth lines in L. rostrata, more pronounced but fewer in number than in L. anatina, appear as shallow rolling “hills” in both the shell and chondrophore. The differences in shell microstructure in these two species are specific to the taxa but based on different habitats and burrowing depths, albeit within the confines of a tropical mangal, could represent biomineralization events that reflect environmental adaptations. Variations in the thickness of the microstructural shell layers of four species of laternulids is compared and we speculate on possible functional and/or environmental relevance of these differences.
3 citations (Crossref) [2023-10-31]
Keywords: dept.aa; peer-reviewed

Promoting collaboration and cultural competence for physician assistant and physical therapist students: A cross-cultural decentralized interprofessional education (IPE) model. - De Oliveira, Kathleen; North, Sara; Beck, Barbra; Hopp, Jane (Journal of Educational Evaluation for Health Professions, 2015)
PURPOSE: As the United States health care model progresses towards medical teams and the country's population continues to diversify, the need for health professional education programs to develop and implement culturally specific interprofessional education (IPE) becomes increasingly imperative. A wide range of models exists for delivering and implementing IPE in health education, but none have included the cultural components that are vital in educating the health professional., METHODS: A cross-cultural decentralized IPE model for physician assistant (PA) and physical therapy (PT) students was developed. This three-part IPE series was created using an established cultural curricular model and began with the exploration of self, continued with the examination of various dimensions of culture, and concluded with the exploration of the intersection between health and culture. We assessed student satisfaction of the IPE experiences and students' engagement and attitudes towards IPE using a three-item open-ended questionnaire administered after each cross-cultural activity and the Interprofessional Education Series Survey (IESS) upon the completion of the series., RESULTS: IESS responses showed that PA and PT students reported benefits in interprofessional collaboration and cultural awareness and expressed overall satisfaction with the series. Qualitative analysis revealed growth in student response depth consistent with the scaffolded focus of each IPE module in the series., CONCLUSION: The trends in this three-part series suggest that institutions looking to develop culturally inclusive IPE educational initiatives may have success through a decentralized model mirroring the effective cultural progression focused on addressing exploration of self, examination of various dimensions of culture, and exploration of the intersection between health and culture.
9 citations (Crossref) [2023-10-31] Place: Korea (South) Oliveira, Kathleen De. Academic Success Center, Southern Connecticut State University, New Haven, CT, USA. North, Sara. Department of Health and Human Movement Sciences, Carroll University, Waukesha, WI, USA. Beck, Barbra. Department of Health and Human Movement Sciences, Carroll University, Waukesha, WI, USA. Hopp, Jane. College of Natural Sciences, Health Sciences and Business, Carroll University, Waukesha, Wisconsin, USA.
Keywords: dept.aa